Implementasi Konsep Context Awareness pada Aplikasi Pengingat Ibadah Sunnah di Platform Android - Muhammad Zaki Nabil; Agi Putra Kharisma; Issa Arwani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
The use of applications installed on smartphones, especially Android, is currently very much used by a Muslim or Muslimah to support prayer activities. One of them is a reminder application for prayer. However, most application reminders are intended only for prayer that is compulsory while the sunnah prayer activities are still relatively small. Another disadvantage is that the application is not able to automatically provide reminders to users that are adjusted to the location, time and activity of the user whether they have performed the prayer or not. For that we need a context-aware concept that is expected to be able to optimize the reminder function so that the application can provide reminders according to user activities. By utilizing context information in the form of location, time, identity and activity of the user through the sensors that are on the smartphone, the application can find out whether the user has carried out prayer or not. Sensors that can be utilized include GPS sensors, proximity sensors, light sensors and accelerometer sensors. The level of efficiency of the use of the application was tested using usability testing and it was found that SUS score of 74 included in good qualifications and success, then in compatibility testing the Sunnah prayer reminders application can run smoothly and there was no error in the Android operating system Lollipop, Marshmallow, Nougat, and Oreo.